National Institutions and Corporate Change: Strategy, Structure and “Systemness” in France, Germany and the United Kingdom, 1950-1993 - Whittington, R; Mayer, M (1999)
This paper distinguishes between `tight' and `loose' perspectives on national business systems. These two systems perspectives are compared in the light of new and existing European data on corporate strategies and structures, on the one hand, and national institutions of business finance, management control and top management development on the other. Despite broadly stable and distinctive institutional backgrounds, European corporations are found to have been transforming their strategies and structures steadily and in very similar ways during the whole post-war period. The paper concludes in favour of loose, rather than tight systems perspectives in contemporary Europe and considers implications for comparative research and economic restructuring.